Motivations and perceived opportunities for partnerships among international business consultancy firms. Issue 4 (4th November 2019) - Kindl, Eva-Maria; Casais, Beatriz
Abstract : Purpose: Consultancy services for internationalisation are crucial to help companies to grow and find new businesses abroad. This kind of service used to be provided by consultancy firms operating in the home country of the clients. Considering the advantages of partnerships that theory has enhanced, this paper aims to identify the motivations and perceived opportunities from consultancy firms to establish business-to-business partnerships with international consultancy companies in other countries, with the purpose of reinforcing international trading. Design/methodology/approach: As an exploratory study, this paper shows the perspective of 13 interviewed German consultancy managers focused on international business about developing a partnership with international consultancy firms from Portugal. Findings: Consultants indicate that with mutual benefits, partnerships are welcome. However, the study enhances the importance of signals of status and reputation for international partnerships among business consultancy firms and reveals a lack of knowledge about the market opportunities for internationalisation that might motivate German consultancy firms to establish partnerships with consultancy companies in Portugal. Originality/value: The paper highlights the low motivation of consultants from a higher-status country to establish partnerships with international business consultancy firms in lower-status countries. The study addresses useful recommendations for consultancy firms, governments and international trade agencies to intensify marketing activities and enhance country reputation and positioning in international business, communicating the opportunities and potential of markets and building signals of status and reputation for international consulting.